Pengaruh Pemberdayaan, Kepemimpinan Transformasional dan Keadilan Organisasional terhadap Komitmen Organisasional Karyawan - Suardani, Ni Made Desi; Supartha, I Wayan Gede (E-Jurnal Manajemen; Vol 7 No 3 (2018)DO - 10.24843/EJMUNUD.2018.v7.i03.p11, 2018)
This study aims to describe the influence of empowerment, transformational leadership and organizational justice to organizational commitment at the Nu Lazer Restaurant and Bar. Samples used were as 43 people were determined with saturated sampling. Questionnaires were distributed as many as 43 pieces and 40 pieces were returned with a response rate of 93.02 percent . Data collection techniques used questionnaires to measurement using a Likert scale and were analyzed data by using multiple linear regression. The results showed that the variables of empowerment, transformational leadership and organizational justice positive and significant effect on organizational commitment. The company must pay attention to the empowerment, transformational leadership and organizational justice to improve organizational commitment.